Expression of MYCN in Multipotent Sympathoadrenal Progenitors Induces Proliferation and Neural Differentiation, but Is Not Sufficient for Tumorigenesis. - Bret C Mobley; Minjae Kwon; Bradley R Kraemer; F Edward Hickman; Jingbo Qiao; Dai H Chung; Bruce D Carter (PLoS ONE, 2015)
Neuroblastoma is a pediatric malignancy of the sympathetic ganglia and adrenal glands, hypothesized to originate from progenitors of the developing sympathetic nervous system. Amplification of the MYCN oncogene is a genetic marker of risk in this disease. Understanding the impact of oncogene expression on sympathoadrenal progenitor development may improve our knowledge of neuroblastoma initiation and progression. We isolated sympathoadrenal progenitor cells from the postnatal murine adrenal gland by sphere culture and found them to be multipotent, generating differentiated colonies of neurons, Schwann cells, and myofibroblasts. MYCN overexpression in spheres promoted commitment to the neural lineage, evidenced by an increased frequency of neuron-containing colonies. MYCN promoted proliferation of both sympathoadrenal progenitor spheres and differentiated neurons derived from these spheres, but there was also an increase in apoptosis. The proliferation, apoptosis, and neural lineage commitment induced by MYCN are tumor-like characteristics and thereby support the hypothesis that multipotent adrenal medullary progenitor cells are cells of origin for neuroblastoma. We find, however, that MYCN overexpression is not sufficient for these cells to form tumors in nude mice, suggesting that additional transforming mutations are necessary for tumorigenesis.